Unique advantages of zebrafish larvae as a model for spinal cord regeneration - Alper, Samuel R.; Dorsky, Richard I. (Frontiers in Molecular Neuroscience, 2022)
The regenerative capacity of the spinal cord in mammals ends at birth. In contrast, teleost fish and amphibians retain this capacity throughout life, leading to the use of the powerful zebrafish model system to identify novel mechanisms that promote spinal cord regeneration. While adult zebrafish offer an effective comparison with non-regenerating mammals, they lack the complete array of experimental approaches that have made this animal model so successful. In contrast, the optical transparency, simple anatomy and complex behavior of zebrafish larvae, combined with the known conservation of pro-regenerative signals and cell types between larval and adult stages, suggest that they may hold even more promise as a system for investigating spinal cord regeneration. In this review we highlight characteristics and advantages of the larval model that underlie its potential to provide future therapeutic approaches for treating human spinal cord injury.